2001
DOI: 10.3141/1757-06
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Soil Stabilization with Liquid Ionic Stabilizer

Abstract: Numerous commercial suppliers are marketing liquid chemical products for stabilizing pavement subgrade and base soils. These nontraditional chemical stabilizers may offer viable alternatives for stabilizing sulfate-rich soils where conventional lime or cement treatment can lead to excessive soil expansion. Typically sold as concentrated liquids that are diluted in water before application, these products may be less expensive to use than lime or cement. However, many transportation agencies are hesitant to spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 7 publications
1
47
0
Order By: Relevance
“…On the other hand, it was clear that for the samples treated with higher MgCl 2 content (more than 5 %), a lower compressive strength was achieved. This was probably due to the increase in the positive surcharge and the subsequent repulsion of soil particles inside the mixture Tingle and Santoni 2003;Katz et al 2001;Rauch et al 2002;Tingle et al 1989). The degradation of strength could also have been due to the amount of alkaline stabilizer (pH value=10), which exceeded the requirement for chemical reaction in the samples Sukmak et al 2013).…”
Section: Compaction Ucs and Direct Shear Testsmentioning
confidence: 99%
“…On the other hand, it was clear that for the samples treated with higher MgCl 2 content (more than 5 %), a lower compressive strength was achieved. This was probably due to the increase in the positive surcharge and the subsequent repulsion of soil particles inside the mixture Tingle and Santoni 2003;Katz et al 2001;Rauch et al 2002;Tingle et al 1989). The degradation of strength could also have been due to the amount of alkaline stabilizer (pH value=10), which exceeded the requirement for chemical reaction in the samples Sukmak et al 2013).…”
Section: Compaction Ucs and Direct Shear Testsmentioning
confidence: 99%
“…These soil stabilizers, although performing satisfactorily in general, have shown some limitations in some situations. For instance, if the soil has excessive sulfate minerals, the reaction between calcium and sulfate will form a mineralettringite (Ca 6 [Al(OH) 6 ]2·(SO 4 ) 3 ·26H 2 O), which causes strength reduction and significant expansion of the soil, which is a commonly reported problem (Mitchell 1986;Katz et al 2001). Besides, the cementitiously stabilized soils are usually very brittle and prone to cracking due to shrinkage or dynamic loading (Little 1992;Sebesta 2005;Li 2014), which greatly lessens the durability and increases the maintenance cost of many applications.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the value of California bearing ratio (CBR) for a mixture of clay and silt increased when treated with 4% epoxy resin agent. Katz et al (2001) and Rauch et al (2002) investigated the effect of three non-traditional agents on treatment of a clay soil. Rauch et al (2002) indicated that there was no significant improving effect of agents (enzymes) on the Atterberg limits, compacted density, shear strength or swell potential, while Katz et al (2001) reported only minor changes in the mechanical behaviour of the soil.…”
Section: Introductionmentioning
confidence: 99%